Efficacy comparison of different moxibustion treatments for allergic rhinitis: A systematic review and Bayesian network meta-analysis. Issue 9 (3rd March 2023) - Chen, Ke; Hou, Chaofeng; Liu, Chengjiang; Meng, Yong
Abstract : Background: At present, there are many commonly used moxibustion methods in clinical practice, but it is unclear which moxibustion is more suitable for the treatment of allergic rhinitis (AR), so we used a network meta-analysis to analyze the effectiveness of various moxibustion types in the treatment of AR. Methods: We searched 8 databases for comprehensive inclusion of randomized controlled trials (RCTs) for moxibustion in the treatment of allergic rhinitis. The search time was from the beginning of database establishment to January 2022. The Cochrane Risk of Bias tool was used to analyze the risk of bias of the included RCTs. Bayesian network meta-analysis of the included RCT was performed using the R software GEMTC and the RJAGS package. Results: A total of 38 RCTs were included, involving 4257 patients and 9 types of moxibustion. The network meta-analysis results revealed that heat-sensitive moxibustion (HSM) not only has the best effect in terms of effective rate (Odd ratio [OR]: 32.77, 95% Credible intervals [CrIs]: 1.86–1360.2) among the nine types of moxibustion, but also has good effect in improving the quality of life score (standard mean differences [SMD]: 0.6, 95% CrIs: 0.07–1.29). In terms of improving IgE and VAS scores, various types of moxibustion were comparable to the efficacy of western medicine. Conclusion: The results showed that HSM was the most effective treatment for AR compared with other types of moxibustion. Therefore, it can be regarded as a complementary and alternative therapy for AR patients with poor effects of traditional treatment and patients who are susceptible to adverse reactions of western medicine.